2012
DOI: 10.1002/jat.2803
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and toxicity: recent findings and future challenges

Abstract: Ghrelin is a novel brain-gut peptide that plays various roles in mammals, including control of food intake and growth hormone release, as well as gastric motility and acid secretion in the gastrointestinal tract. It is mainly secreted by the gastric mucosa, but is also expressed in various other tissues. Different studies confirm the multiple biological roles of and possible protective effects of ghrelin. Multiple in vitro and in vivo studies support the powerful protective action of ghrelin against heart, gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Because the survival increases in Peg-G-CSF-treated RI mice is around 30% above the vehicle-treated counterpart group ( Kiang et al, 2014a ), the object of this project was to investigate remedies that could enhance Peg-G-CSF efficacy in treating RI. Ghrelin was selected for this purpose because this co-therapy has been reported to reduce the RI-induced brain hemorrhage ( Kiang et al, 2019 ; Gorbunov and Kiang, 2021 ) and Ghrelin alone was effective for other organ diseases ( Wynne et al, 2005 ; Vasileious et al, 2013 ; Pereira et al, 2017 ; Fritz et al, 2020 ). Ghrelin is a peptide containing 28 amino acids; it is produced in the stomach during hunger and released into the blood stream to go to the hypothalamus for initiating the desire of food intake ( Wynne et al, 2005 ; Vasileious et al, 2013 ; Pereira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the survival increases in Peg-G-CSF-treated RI mice is around 30% above the vehicle-treated counterpart group ( Kiang et al, 2014a ), the object of this project was to investigate remedies that could enhance Peg-G-CSF efficacy in treating RI. Ghrelin was selected for this purpose because this co-therapy has been reported to reduce the RI-induced brain hemorrhage ( Kiang et al, 2019 ; Gorbunov and Kiang, 2021 ) and Ghrelin alone was effective for other organ diseases ( Wynne et al, 2005 ; Vasileious et al, 2013 ; Pereira et al, 2017 ; Fritz et al, 2020 ). Ghrelin is a peptide containing 28 amino acids; it is produced in the stomach during hunger and released into the blood stream to go to the hypothalamus for initiating the desire of food intake ( Wynne et al, 2005 ; Vasileious et al, 2013 ; Pereira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is capable of modulating appetite, energy and glucose metabolism, gastrointestinal, immune and cardiovascular functions and cell proliferation (Leite-Moreira and Soares, 2007). It is also implicated in many pathogeneses such as type II diabetes based on the modification in either its receptor concentration or expression (Bolkent et al, 2006;Vasileiou et al, 2013). Obestatin is a 23-amino-acid-peptide derived from the carboxy-terminal part of the ghrelin gene.…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin has several physiological functions, including secretion of GH ( Kojima et al , 1999 ; Nagaya et al , 2001 ) and insulin-like growth factor-1 (IGF-1; Akamizu and Kangawa, 2006 ; Veldhuis et al , 2008 ), promotion of the appetite signal, and stimulation of gastrointestinal activity in humans ( Takata et al , 2015a ). In addition, both in vivo and in vitro studies have shown that ghrelin, via promoting IGF-1 release, exerts a powerful protective effect against damage of the heart, gastrointestinal tract, liver, nervous system, and kidney ( Gobe et al , 1999 ; Takeda et al , 2006 ; Vasileiou et al , 2013 ).…”
mentioning
confidence: 99%